Students’ e-worksheet based on project and Character of Pancasila through environmental issues: What are the characteristics? - Dede Nurhidayah; Anggi Tias Pratama (Research and Development in Education (RaDEn), 2024)
This research aimed to describe the character of project-based learning that uses e-worksheets with the integration of Pancasila values. This qualitative descriptive research uses interview techniques, observation, and literature study in data collection. Based on the observation results, each feature of the Pancasila student profile dimension was reflected in the learning syntax with the expected development criteria. The project-based learning is beneficial in developing the Character of Pancasila through the student strengthening project. Characteristics of project-based learning include: (1) independently, from planning, preparation, and manufacture to product presentation; (2) full responsibility for the project created; (3) involving peers, teachers, parents, and even the community; (4) train students' critical and creative thinking skills; and (5) space for dissemination of ideas. The Pancasila learner profile's dimensions are reflected in the electronic learner worksheet, within each project-based learning syntax presented in learning activities. The syntax for project-based learning includes (1) basic questions; (2) designing project planning; (3) developing a schedule; (4) monitoring project activity and development; (5) testing results; and (6) evaluating the learning experience. By following this syntax, students are expected to develop the dimensions of the Pancasila learner profile, which include: (1) believing in and fearing God, and having noble character; (2) embracing global diversity; (3) working collaboratively; (4) being independent; (5) critical reasoning; and (6) being creative.